FACTORS AFFECTING AUDITOR SWITCHING WITH FINANCIAL DISTRESS AS A MODERATING VARIABLE IN JAKARTA ISLAMIC INDEX 70 COMPANIES FOR THE PERIOD 2019-2023 - Delvina Hotmatullayni Siregar; Keulana Erwin; Yeni Absah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The purpose of this study is to determine and analyze the effect of management turnover, audit fees and company size on auditor switching in Jakarta Islamic Index 70 companies for the 2019-2023 period. In addition, this study also aims to analyze whether financial distress is able to moderate the relationship between management turnover, audit fees and company size on auditor switching. The type of research conducted is quantitative research. The population in this study were companies incorporated in the Jakarta Islamic Index for the period 2019-2023 totaling 135 companies. The sample in this study were 25 companies incorporated in the Jakarta Islamic Index in 2019-2023 which were obtained by purposive sampling technique. The data collection method used in this research is the literature study method and documentation. The data analysis method used in this research is Logistic Regression Analysis with the help of Eviews 13 software. The results obtained in this study indicate that management change is proven to have a positive and significant influence on auditor switching of the Jakarta Islamic Index 70 (JII70) company for the 2019-2023 period. Audit fees and company size proved to have no significant effect on auditor switching. Financial distress is proven to be able to strengthen the influence of management turnover and audit fees on auditor switching. While other results show that financial distress proved unable to strengthen the influence of company size on auditor switching of the Jakarta Islamic Index 70 (JII70) company for the period 2019-2023.